Hydrophobization of fully bio-based epoxy polymers using water as solvent : effect of additives - Bellido-Aguilar, Daniel Angel (2021)
Current epoxy industry still has a strong dependency on fossil-derived precursors as demonstrated in the use of bisphenol A-based resins. To improve the sustainability of the epoxy industry, bio-based chemicals have been explored for the synthesis of environmentally-friendly epoxy polymers. This paper reports the hydrophobization of fully bio-based epoxy coatings using only water as solvent. Three bio-based additives (hexanoic acid, resveratrol, and a cardanol-based epoxy resin) were studied aiming to enhance the hydrophobicity of the coatings. The curing reaction mechanisms have been extensively explored. The modified coatings showed better hydrophobicity, however, they tend to possess a lower crosslink density because these additives have, to some extent, disrupted the polymer network formation. The anticorrosion performance of the bio-based coatings was also evaluated and discussed based on the reported hydrophobicity and crosslink density. This study lays a foundation towards fully bio-based, environmentally-friendly polymers for hydrophobic applications in the future.